Effect of corrosion on fatigue behaviour of aluminum alloys - Navin Manoharan (2013)
Corrosion has been and still is a worldwide problem today. Not only has it cost governments and companies millions of dollars, many have lost their lives due to the effects of corrosion on various man-man structures. These structures like bridges and aircraft experience fatigue stresses that causes the periodic propagation of cracks, leading to eventual failure. It has been well documented that corrosion acts as an existing defect, expediting fatigue failure by reducing the number of stress cycles it can withstand at a given stress level. Due to its superior strength to weight ratio, Aluminum is increasingly used in many such structures especially aircraft. 2 commonly used alloys AA2524 and AA7075 were thus analyzed to characterize pitting corrosion.